The Influence of Product Attribute and Reference Group Towards Customer Value of Moslem’s Wear Kerawang Handycraft In Gorontalo Province - Muchtar Ahmad (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
This aims of the: (1) The customers responses toward the product attribute of value the Moslem wears of kerawang handycraft in Gorontalo province, (2), The influence of the refence group to toward the customers value of kerawang handycraft Moslem’s wear in Gorontalo Province, (3), The influence of the products attribute and reference group toward the customers value of the kerawang handycraft of moslem’s in Gorontalo province, in a partial or in simultaneous. The research has tested the hypothesis of attribute influence products and reference group towards customer value kerawang handycraft moslem’s wear in Gorontalo province, in a partial or in simultaneous. The research used explanatory survey. The study examined 86 customers of kerawang handycraft moslem’s wear. The sampling method was used the random sampling technique. The result of the study was analyzed by using the path analysis, statistic hypothesisis tested by F test and t test. The result of the research shows that kerawang handycraft especially moslem’s wear, product attribute and the reference group partial is as ways or in simultaneously influenced the customers value of in Gorontalo Province. Keywords: Product Attribute, Reference Group and Customer Value